Optimización de equipo triturador de envases de vidrio con capacidad 130 kg/h, para la empresa schott envases farmaceuticos s.a.s (2021)
The continuous mechanical complications and difficult operation that the rejected container crushing machine presented, created the imminent need to optimize the equipment, to achieve greater availability, efficiency and reduction in maintenance costs, for which the implementation of a conveyor belt was formulated as new lifting mechanism for the containers, for the container crusher it was proposed to increase the number of hammers so as to increase efficiency and additionally change the type of steel in which the impact hammers are built to achieve greater durability. Conveyor belts turn out to be highly appropriate equipment for the transport of bulk materials, their configurations offer numerous possibilities, including the ascent or descent of material, in this document the calculation and selection of the elements that make up the implemented conveyor belt were developed. and through which the transport of the containers will be carried out until they are deposited inside the shredder, the shredding is a process by which the size of an element or material is reduced, in this case the glass containers are disintegrated by impacts generated by the hammers located on the drive shaft. With the implementation of the belt conveyor, it was achieved that the containers did not break before entering the shredder, this eliminated the conditions of physical contamination (glass particles) in the moving elements of the equipment and in the work area, thus avoiding the Premature wear of mechanisms, increasing equipment availability, and eliminating unsafe process conditions, additionally a 50% reduction in annual equipment maintenance costs was achieved. The crushing chamber increases its efficiency by 16% avoiding reprocessing this thanks to the incorporation of eleven new impact hammers and a new distribution, AISI/SAE 4140 steel gives impact hammers greater resistance to abrasive wear compared to steel AISI/SAE 1020.